1984
DOI: 10.1007/bf02534482
|View full text |Cite
|
Sign up to set email alerts
|

Sterol metabolism in the nematodeCaenorhabditis elegans

Abstract: The metabolism of various dietary sterols and the effects of an azasteroid on sitosterol metabolism in the free-living nematodeCaenorhabditis elegans was investigated. The major unesterified sterols ofC. elegans in media supplemented with sitosterol, cholesterol or desmosterol included 7-dehydrocholesterol (66.5%, 40.5%, 31.2%, respectively), cholesterol (6.7%, 52.3%, 26.9%), lathosterol (4.4%, 3.6%, 1.7%) and 4α-methylcholest-8(14)-en-3β-ol (4.2%, 2.1%, 3.8%). Esterified sterols, representing less than 20% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Although nat-cholesterol alone satisfies the C. elegans sterol requirement, C. elegans can transform cholesterol into other sterols, most notably 7-dehydrocholesterol (12). Consequently, a metabolite of cholesterol, even if structurally quite similar to cholesterol, may perform an unknown specific, critical function.…”
Section: Table Imentioning
confidence: 99%
“…Although nat-cholesterol alone satisfies the C. elegans sterol requirement, C. elegans can transform cholesterol into other sterols, most notably 7-dehydrocholesterol (12). Consequently, a metabolite of cholesterol, even if structurally quite similar to cholesterol, may perform an unknown specific, critical function.…”
Section: Table Imentioning
confidence: 99%
“…The analysis of worm sterols by GC-mass spectrometry or by TLC analysis of worms fed with radioactive cholesterol demonstrated that the bulk of exogenously added sterol remains unchanged; [8][9][10] however, C. elegans is able to carry out some modifications on them. [6,[8][9][10][11][12][13][14][15] Thus, several enzymatic transformations of cholesterol were identified and the major metabolic pathway in C. elegans was outlined.…”
Section: Introductionmentioning
confidence: 99%
“…[6,[8][9][10][11][12][13][14][15] Thus, several enzymatic transformations of cholesterol were identified and the major metabolic pathway in C. elegans was outlined. [14] In this context, two transformations should be emphasized: the dehydrogenation of cholesterol at position 7 (production of 7-dehydrocholestrol) and methylation at position 4 (production of lophenol) (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…1D), it is not known exactly when depletion first occurs because we have not yet performed a time course study measuring sterols in worms treated with Aza. Second, in an earlier report, several different sterols in C. elegans were depleted by Aza treatment; cholesterol was depleted to ϳ1% of the level typically found in C. elegans after culturing with a concentration of Aza approximately one-half that used in the present study (47). From the results from our laboratory, it was observed that a transgenic worm, called cholegans, which can produce endogenous cholesterol by converting 7-dehydrocholesterol showed a 30% increase in MLS when grown in the cholesterol depletion condition (56).…”
Section: Discussionmentioning
confidence: 42%
“…Acute Toxicity of Aza on C. elegans Development-The disturbance of sterol metabolism in C. elegans by Aza toxicity has been well documented (1,3,47,48). Our investigation addressed the biochemical and cellular mechanism underlying Aza toxicity, focusing on Aza toxicity in the second generation (F2) after initial Aza treatment of parental worms (P0).…”
Section: Resultsmentioning
confidence: 99%